CARCASS OF NATIVE CHICKEN DUE TO FEEDING CONTAINS EXPIRED MILK - I M., NURIYASA; PERTIWI, M. E. D.; PUGER, A. W.; PUSPANI, E. (Majalah Ilmiah Peternakan; Vol 23 No 3 (2020): Vol. 23 No. 3 (2020), 2020)
This study aims to determine the effect of replacing fish meal with expired milk in rations on native chicken carcass. The experimental design used in this study was a completely randomized design (CRD), with five treatments and five replications, each experimental unit consisting of four male native chickens. The treatments were ration without replacement of fish meal (R0); ration replacement of 25% fish meal with expired milk (R1); ration for 50% replacement of fish meal with expired (R2); ration for replacement of 75% fish meal with expired milk (R3) and ration for replacing 100% fish meal with expired milk (R4). Rations and water were given ad libitum. The variables observed were carcass and carcass physical composition. The results showed that carcass weight and meat weight of treatment R3 were higher (P<0.05) than R4, R2, R1 and R0. All treatments had no significant different (P>0.05) on the commercial carcass. The study concluded that replacing fish meal with expired milk at the level of 75% resulted in higher carcass than other treatments.